(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The objective of this article is to analyse the relation ship between Communication and Information Technologies (ICT) and economic growth. ICT play a relevant paper since the last decades being, therefore, important to study their effects on one of the most important economic policy goals. Due to the difficulty to establish a direct relationship between both, we have analysed the ICT efefcts on social capital and entrepreneurship, that have also effects on economic growth. It is shown that the policies designed to foster ICT have effects on economic growth through those two factors.